The reliability of rock mass classification systems as underground excavation support design tools - Ranasooriya, Jayantha (Curtin University, 2009)
This thesis examines the reliability of rock mass classification systems available for underground excavation support design. These methods are sometimes preferred to rational methods of support design particularly if detailed information required for the latter mentioned methods is lacking. The classification approach requires no analysis of any specific failure mechanisms or the forces required to stabilise unstable rocks, yet, the support measures thus designed are considered to deal with all possible failure mechanisms in a rock mass.Amongst the several rock mass classification methods developed for application in underground excavation engineering, two have stood out. These are known as rock mass rating (RMR) and tunnelling quality index (Q), introduced by Bieniawski (1973) and Barton et al. (1974), respectively. Over the years, the two methods have been revised and updated so as to improve their reliability as support design tools, yet the two methods are know to have limitations and their reliability has long been a subject of considerable debate. Nevertheless, attempts to assess their reliability in a systematic manner have been limited. Further, some practitioners in the field of rock engineering continue to use these methods as the sole methods of support design for underground rock excavations. The objective of thesis, therefore, is to contribute to a better understanding of the reliability of the two classification methods.This study considered that the reliability of the RMR and Q methods can be assessed by comparing their support predictions with those derived by other applicable methods and also with the actual support installed. Such an assessment can best be carried out during excavation of an underground opening because representative data can be collected by direct observation of the as-excavated ground conditions and monitoring the performance of the support installed. In this context, the geotechnical data obtained during the construction of several case tunnels were reviewed and the two classification methods were applied. The effectiveness of their support predictions was then evaluated against the potential failures that can be predicted by some of the applicable rational methods. Since the rock masses intersected in the case tunnels are jointed, mostly the structurally controlled failure modes were analysed. The support measures predicted by the two methods were compared with each other and with the actual support installed in the case tunnels. Further, the RMR and Q vales assigned to the case tunnels were correlated to observe any relationship between the two.The study showed that the RMR and Q predicted support measures are not always compatible. In some circumstances, the two methods can either overestimate or under estimate support requirements.